2022
DOI: 10.1016/j.ecolmodel.2021.109844
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structure of natural boxwood and the invasive box tree moth can promote coexistence

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Spatially local interactions can in uence ecological processes including disease, predation, and resource competition (DeAngelis and Yurek, 2017), and other authors have also found that movement is a key determinate of how local interactions scale up to population-level effects (eg. Pacala and Silander 1990; Lin and Pennings, 2018; Ledru et al, 2022). Our results further illustrate how understanding the relative scales of habitat heterogeneity and animal movement is critical to determining how spatially local interactions impact ecological dynamics.…”
Section: Discussionmentioning
confidence: 57%
“…Spatially local interactions can in uence ecological processes including disease, predation, and resource competition (DeAngelis and Yurek, 2017), and other authors have also found that movement is a key determinate of how local interactions scale up to population-level effects (eg. Pacala and Silander 1990; Lin and Pennings, 2018; Ledru et al, 2022). Our results further illustrate how understanding the relative scales of habitat heterogeneity and animal movement is critical to determining how spatially local interactions impact ecological dynamics.…”
Section: Discussionmentioning
confidence: 57%
“…Spatially local interactions can influence ecological processes including disease, predation, and resource competition [ 28 ], and other authors have also found that movement is a key determinate of how local interactions scale up to population-level effects (eg. [ 52 , 54 , 64 ]). Our results further illustrate how understanding the relative scales of habitat heterogeneity and animal movement is critical to determining how spatially local interactions impact ecological dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive species may reach spectacular densities. During population outbreaks, the box tree moth becomes so numerous that predators are unlikely to influence their morph frequencies ( Ledru et al, 2022 ; Poloni, unpublished data). However, once caterpillars have defoliated all available hosts, moth populations drop and persist at lower densities according to the recovery of food plants ( Suppo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%